Coronavirus (COVID-19): guidance on phased return of sport and recreation (Department for Digital, Culture, Media and Sport, 2020)
Guidance for the public, providers of outdoor sport facilities, elite athletes, personal trainers and coaches on the phased return of sport and recreation.